Linear flow in an elastoviscoplastic cylindrical layer under single side adhesion conditions - Panchenko, Galina Leonidovna (Computational Continuum Mechanics, 2011)
The paper presents exact solutions to a series of boundary value problems of the theory of large deformations considering the viscoplastic flow of an elastoviscoplastic material in the space between two rigid coaxial cylindrical surfaces when one of the surfaces moves. It is assumed that there is a slip of the material on one of the surfaces. The analysis is carried out to study the reversible deformation, the development of a viscoplastic flow under conditions where each surface is in uniformly accelerated motion, and the retardation of the flow to a full stop and complete unloading of the medium in the case of the uniformly retarded motion of surfaces.